DEVELOPMENT OF A NANO PARTICLE VACCINE TO PREVENT ZIKA VIRUS INFECTION - Ethan Tan; Lucas Wong; Ryan Teo; Muntasir Muntasir (Yayasan Adra Karima Hubbi, 2025)
Zika virus is a mosquito-borne flavivirus that causes severe birth defects in newborns. Effective preventive measures are urgently needed due to the global spread of the virus. To develop a nanoparticle-based vaccine to prevent Zika virus infection by enhancing immune responses and ensuring safety. A multidisciplinary approach combining virology, immunology, and nanotechnology was used. Laboratory animals and human volunteers were included in the study. The nanoparticle vaccine was characterized using DLS and electron microscopy, and its immunogenicity was tested using ELISA and flow cytometry. Preclinical and clinical trials were conducted to assess the vaccine's efficacy and safety. The nanoparticle vaccine induced strong and long-lasting immune responses, reducing Zika virus infection rates by 85% in mice and 80% in non-human primates. The vaccine showed high titers of neutralizing antibodies and significant cellular immune responses without adverse effects. The nanoparticle vaccine demonstrated high efficacy and safety in preventing Zika virus infection, providing a promising new approach to vaccine development. Further clinical trials are needed to validate these findings and optimize vaccine production for widespread use.